The Authority of the Regional Government in Preserving the Cultural Heritage of Gedung Juang 45 is Based on Serang City Regional Regulation Number 6 of 2021 concerning the Preservation of Cultural Heritage - Fadila, Bilqis Safa (Beleid, 2023)
The Indonesian nation is a highly cultured nation and this culture is valuable for civilization. The state must respect, preserve, protect and develop national culture. The problem is first, how is the authority of the Regional Government in preserving the cultural heritage of Gedung Juang 45 Serang City based on Serang City Regional Regulation Number 6 of 2021 concerning Cultural Heritage Preservation. Second, what are the obstacles and efforts of the Regional Government in preserving the cultural heritage of Gedung Juang 45 Serang City based on Serang City Regional Regulation Number 6 of 2021 concerning Cultural Heritage Preservation. The theory used is the theory of authority and The theory of preservation of cultural heritage. The research method is the empirical juridical legal method. The research specification used is analytical descriptive research. Data sources are primary data research and secondary data. Collection techniques Data is carried out by literature research and field research. Data obtained in this writing uses a qualitative descriptive way, namely analysis that describes or explains the existing rules or regulations, basic principles and applicable theoretical theories. Conclusion of the study on the authority of the Regional Government in the preservation of the cultural heritage of Gedung Juang 45 The Regional Government is authorized to preserve the cultural heritage of Gedung Juang 45 in Serang City in regulating and managing its own government affairs and must be based on law. Second, the constraints are the budget aspect that is not enough for maintenance and the street vendors who sell around Juang 45 Building in Serang City. Meanwhile, the effort is the need for government support to pay attention to the damage that exists in cultural heritage buildings, and also supervise the protection, development, utilization and implementation of revitalization and adaptation of cultural heritage buildings, cultural heritage structures, and cultural heritage areas. The advice given by the author is that the Government should provide more support to pay more attention to cultural heritage and the Government should make an appeal and socialization to pay more attention to cultural heritage objects.